Analisis Penentuan Sektor Unggulan Perekonomian di Kabupaten Kubu Raya - Hajeri, Hajeri; Yurisinthae, Erlinda; Dolorosa, Eva (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
This research intends to determine leading sectors in the Regency Kubu Raya. Leading sectorscan be determined by combining some analysis tools, such as: Typology Klassen, combinedLocation Quotient dan Dynamic Location Quotient,  Shift Share. Time series data is used in thisresearch, such as PDRB of Kubu Raya Regency and West Borneo Province from 2008 to 2013based on constant basic price. The result of this research showed that  leading sectors economy inKubu Raya Regency based on combined analysing from three analysis tools are transport andcommunications sector. Potential sector to be developed to become  leading sectors in the futureare processing industry, elictricity, gas, and clean water sector. Meanwhile, from the fiveagriculture sub sectors in Kubu Raya Regency based on combined analysis from the threeanalysis tools showed that livestock sub sector has potential to be developed to become a leadingsector economy in Kubu Raya Regency.